(untitled) (Revista de História da UEG (REVHIST), 2021)
The protection of possessions of peasants in Brazil was influenced by the enactment of Law nº. 601 of September 18, 1850, Law of Property Land disciplinarian. These changes initially caused no impact on social relations in the Legal Amazon, that because of the vastness of the territory, the low population density, and the lack of an efficient road network to connection with rest of the country, however, in the decades from 1950 - 1980 agrarian conflicts erupted in the region, especially in Maranhão, influenced by the doctrine of the State Law nº. 2.979/1969, Law Land Sarney. This exploratory study based on literature review seeks to clarify the influences of these rules on conditions for reproduction and survival of the peasantry in Maranhão. Keywords: Maranhão. Possessions of peasants. Peasantry. Agrarian conflicts.